Expression of spidroin proteins in the silk glands of golden orb‐weaver spiders. Issue 4 (4th January 2022) - Jorge, Inmaculada; Ruiz, Víctor; Lavado‐García, Jesús; Vázquez, Jesús; Hayashi, Cheryl; Rojo, Francisco J.; Atienza, José M.; Elices, Manuel; Guinea, Gustavo V.; Pérez‐Rigueiro, José
Abstract: The expression of spidroins in the major ampullate, minor ampullate, flagelliform, and tubuliform silk glands of Trichonephila clavipes spiders was analyzed using proteomics analysis techniques. Spidroin peptides were identified and assigned to different gene products based on sequence concurrence when compared with the whole genome of the spider. It was found that only a relatively low proportion of the spidroin genes are expressed as proteins in any of the studied glands. In addition, the expression of spidroin genes in different glands presents a wide range of patterns, with some spidroins being found in a single gland exclusively, while others appear in the content of several glands. The combination of precise genomics, proteomics, microstructural, and mechanical data provides new insights both on the design principles of these materials and how these principles might be translated for the production of high‐performance bioinspired artificial fibers. Abstract : Genomics and proteomics data are combined to establish the expression pattern of spidroins in the silk glands of Trichonephila clavipes . Research highlights: ‐ Proteomics was used to analyse the spidroin content of MA, mi, Flag and Tub glands. ‐ Peptides were compared with spidroin genes. ‐ Only a fraction of the genes is expressed in the glands. ‐ Two proteins were identified in the four glands.